Astrocyte Role in Temporal Lobe Epilepsy and Development of Mossy Fiber Sprouting - Twible, Carolyn; Abdo, Rober; Zhang, Qi (Frontiers in Cellular Neuroscience, 2021)
Epilepsy affects approximately 50 million people worldwide, with 60% of adult epilepsies presenting an onset of focal origin. The most common focal epilepsy is temporal lobe epilepsy (TLE). The role of astrocytes in the presentation and development of TLE has been increasingly studied and discussed within the literature. The most common histopathological diagnosis of TLE is hippocampal sclerosis. Hippocampal sclerosis is characterized by neuronal cell loss within the Cornu ammonis and reactive astrogliosis. In some cases, mossy fiber sprouting may be observed. Mossy fiber sprouting has been controversial in its contribution to epileptogenesis in TLE patients, and the mechanisms surrounding the phenomenon have yet to be elucidated. Several studies have reported that mossy fiber sprouting has an almost certain co-existence with reactive astrogliosis within the hippocampus under epileptic conditions. Astrocytes are known to play an important role in the survival and axonal outgrowth of central and peripheral nervous system neurons, pointing to a potential role of astrocytes in TLE and associated cellular alterations. Herein, we review the recent developments surrounding the role of astrocytes in the pathogenic process of temporal lobe epilepsy and mossy fiber sprouting, with a focus on proposed signaling pathways and cellular mechanisms, histological observations, and clinical correlations in human patients.